Music and gender construction: analysis of Jenny Rivera's songs (Revista de Investigaciones Universidad del Quindío, 2022)
Objective: To analyze the content of the songs performed by the singer Jenny Rivera, where female gender roles are represented, in her acting with other women and her relationship with the male figure. The artistic and cultural universes with the viscerality and emotionality of the human being, it is evident and practically impossible not to draw links between how music is related to mental health. And although we can witness the ways in which the art of sound and silence enters our brain to generate "positive" and "negative" emotional reactions, rarely are we truly aware of the way this happens and the role so important that music can charge in our mental health (Rios, 2019).Material and Method: The qualitative content analysis of a sample of 10 songs was used, which have this theme. Results: In the songs analyzed, we realize how the same woman encourages her fellow men the wrong ways and means of assuming and confronting couple situations. Encouraging violence not only physical, but psychological towards herself, as well as the denigration of her own female figure. The discourse and content of each of these songs, along with the type of music (band), come together to give it a more significant value, that without taking into account the places where these types of songs are mostly heard. Conclusions: With this work we can conclude that this type of songs in the future could be analyzed and passed through formal musical filters, to really be able to produce them and bring them to the market.
Keywords: Mental Health; Gender; Music